2020
DOI: 10.3389/fgene.2020.00502
|View full text |Cite
|
Sign up to set email alerts
|

WISP1 Predicts Clinical Prognosis and Is Associated With Tumor Purity, Immunocyte Infiltration, and Macrophage M2 Polarization in Pan-Cancer

Abstract: Cancer is becoming the leading cause of death and a major public health problem. Although many advanced treatment strategies are currently in use, the general prognosis of cancer patients remains dismal due to the high frequency of recurrence, metastasis. The identification of effective biomarkers is important for predicting survival of cancer patients and improving treatment efficacy. In this study, we comprehensively analyzed WNT1-inducible-signaling pathway protein 1 (WISP1) expression and explored its corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…Meanwhile, we also found that more than 10 genes associated with M1 phenotype were expressed significantly lower in P4 macrophages than P3 vice versa ( Figure 4 D). Gene regulation in macrophages for M1- and M2-associated phenotypes were previously described [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, we also found that more than 10 genes associated with M1 phenotype were expressed significantly lower in P4 macrophages than P3 vice versa ( Figure 4 D). Gene regulation in macrophages for M1- and M2-associated phenotypes were previously described [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, we also found that more than 10 genes associated with M1 phenotype were expressed significantly lower in P4 macrophages than P3 vice versa (Figure 4D). Gene regulation in macrophages for M1-and M2-associated phenotypes were previously described [32][33][34][35][36][37][38][39]. However, there were no significant changes between P3 and P4 macrophages in the reaction with further IL-10 stimulus.…”
Section: A Selective Pressure For Cell Survival Was Initiated After Withholding Of M-csf Supplementmentioning
confidence: 87%
“…To clarify the functions of DEGs, we further performed functional enrichment analysis. The proteins translated by DEGs were mainly located in extracellular regions and these genes were primarily implicated in tumor-related biological processes such as cell adhesion, wound healing, and extracellular matrix organization (Yu et al, 2019;Alfarsi et al, 2020;Liao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To better clarify the functions of DEGs, we further performed functional enrichment analysis. The proteins translated by DEGs were mainly located in extracellular regions and these genes were primarily implicated in tumor-related biological processes such as cell adhesion, wound healing and extracellular matrix organization [16][17][18].…”
Section: Discussionmentioning
confidence: 99%